Extended use of raltegravir in the treatment of HIV-1 infection: optimizing therapy - Charlotte Charpentier; Laurence Weiss (Infection and Drug Resistance, 2010)
Charlotte Charpentier1, Laurence Weiss21Assistance Publique-Hôpitaux de Paris, Hôpital Bichat-Claude Bernard, Laboratoire de Virologie, Université Paris-Diderot, Paris, France; 2Assistance Publique-Hôpitaux de Paris, Hôpital Européen Georges Pompidou, Service d’Immunologie Clinique, Université Paris Descartes, Paris, FranceAbstract: Raltegravir is the first licensed compound in 2007 of the new integrase inhibitor drug class. At the dose of 400 mg twice daily, raltegravir showed a potent antiviral action in antiretroviral-naïve patients when associated with tenofovir and emtricitabine. Raltegravir was also found to be highly active in antiretroviral-experienced patients with virological failure and displaying multiresistant virus, as shown with the BENCHMRK and ANRS 139 TRIO trials. Finally, the use of raltegravir was assessed in the context of a switch strategy in antiretroviral-experienced patients with virological success [human immunodeficiency virus type 1 (HIV-1) RNA below detection limit], highlighting the following mandatory criteria in this strategy: the nucleoside reverse transcriptase inhibitors associated with raltegravir have to be fully active. In the different studies, raltegravir had a favorable safety and tolerability profile. In the clinical situation a switch in virologically suppressed patients receiving a protease inhibitor, an improvement of the lipid profile was observed. Overall, when analyzing the Phase II and III trials together, only a few patients on raltegravir discontinued for adverse events. The development of resistance to raltegravir mainly involved three resistance mutations in integrase gene: Q148H/K/R, N155H, and Y143C/H/R. In conclusion, raltegravir improved the clinical management of HIV-1 infection both in antiretroviral-naïve and in antiretroviral-experienced patients.Keywords: HIV-1, integrase inhibitors, raltegravir, antiretroviral therapy